MEASURING THE EFFECT OF SOME VARIABLES ON THE CONSUMPTION OF ELECTRIC ENERGY IN IRAQ: A STUDY ON DIYALA GOVERNORATEMEASURING THE EFFECT OF SOME VARIABLES ON THE CONSUMPTION OF ELECTRIC ENERGY IN IRAQ: A STUDY ON DIYALA GOVERNORATE - Rasheed, Asmaa m; hassen, waleed A.; Hasan, Ayat S.; Shyaa, Methaq A. (International Journal of Psychosocial Rehabilitation, 2020)
The future prediction of the demand for electricity contributes to solving the problems of the electric power sector through future planning to meet the increase in the demand for electric energy. There is a lot of research that dealt with several methods to predict the future demand for energy. The study relied on the method of the multiple linear regression model and using the (spss program) to find the model by forecasting Several non- certified variables (Xı) were taken, such as (average per capita income. Price per kilowatt sold to the consumer).